Delayed umbilical cord clamping after childbirth: potential benefits to baby's health - Uwins C; Hutchon DJR (Dove Medical Press, 2014)
Christina Uwins,1 David JR Hutchon2 1Department of Obstetrics and Gynaecology, Croydon University Hospital, Croydon, 2Department of Obstetrics, Darlington Memorial Hospital, Darlington, UKAbstract: Early cord clamping was initially introduced as part of the package of care known as “active management of the third stage”, which was implemented to reduce postpartum hemorrhage. It has now been shown to provide no benefit to the mother and to result in harm to the neonate. The clinical trial evidence relating to delayed cord clamping compared to immediate cord clamping is presented and the physiological rationale for delayed cord clamping is discussed in this paper. Most organizations (eg World Health Organization (WHO), Royal College of Obstetricians and Gynaecologists (RCOG), Resuscitation Council (UK),The International Federation of Gynecology and Obstetrics (FIGO), International Confederation of Midwives, International Liaison Committee on Resuscitation (ILCOR) and the European Resuscitation Council) now advise a delay of 1–3 minutes before clamping the cord in term and preterm infants, and clinicians need to be aware of this change. Healthy neonates benefit from a more physiological and gentle transition from placental to pulmonary respiration, and we explain why this benefit should be provided to all neonates until there is any evidence to the contrary. The harm of early cord clamping is not limited to anemia and iron deficiency, and evidence for a wide range of possible harms of early cord clamping is presented. The need for resuscitation is one of the most common concerns, and ways of overcoming these concerns are described.Keywords: transition, cord clamping, hypovolemia, intraventricular hemorrhage